Influence of vitamin B auxotrophy on nitrogen metabolism in eukaryotic phytoplankton - Bertrand, Erin M.; Allen, Andrew E. (Frontiers in Microbiology, 2012)
While nitrogen availability is known to limit primary production in large parts of the ocean, vitamin starvation amongst eukaryotic phytoplankton is becoming increasingly recognized as an oceanographically relevant phenomenon. Cobalamin (B12) and thiamine (B1) auxotrophy are widespread throughout eukaryotic phytoplankton, with over 50% of cultured isolates requiring B12 and 20% requiring B1. The frequency of vitamin auxotrophy in harmful algal bloom species is even higher. Instances of colimitation between nitrogen and B vitamins have been observed in marine environments, and interactions between these nutrients have been shown to impact phytoplankton species composition. This review evaluates the potential for interactive effects of nitrogen and vitamin B12 and B1 starvation in eukaryotic phytoplankton. B12 plays essential roles in amino acid and one-carbon metabolism, while B1 is important for primary carbohydrate and amino acid metabolism and likely useful as an anti-oxidant. Here we will focus on three potential metabolic interconnections between vitamin, nitrogen and sulfur metabolism that may have ramifications for the role of vitamin and nitrogen scarcities in driving ocean productivity and species composition. These include: (1) B12, B1, and N starvation impacts on osmolyte and antioxidant production, (2) B12 and B1 starvation impacts on polyamine biosynthesis, and (3) influence of B12 and B1 starvation on the diatom urea cycle and amino acid recycling through impacts on the citric acid cycle. We evaluate evidence for these interconnections and identify oceanographic contexts in which each may impact rates of primary production and phytoplankton community composition. Major implications include that B12 and B1 deprivation may impair the ability of phytoplankton to recover from nitrogen starvation and that changes in vitamin and nitrogen availability may synergistically impact harmful algal bloom formation.